2013
DOI: 10.1155/2013/794643
|View full text |Cite
|
Sign up to set email alerts
|

MLST Genotypes and Antibiotic Resistance ofCampylobacterspp. Isolated from Poultry in Grenada

Abstract: This study determined whether multilocus sequence types (MLST) of Campylobacter from poultry in 2 farms in Grenada, West Indies, differed by farm, antimicrobial resistance and farm antibiotic use. Farm A used fluoroquinolones in the water and Farm B used tetracyclines. The E-test was used to determine resistance of isolates to seven antibiotics. PCR of the IpxA gene confirmed species and MLST was used to characterize 38 isolates. All isolates were either C. jejuni or C. coli. Farm antibiotic use directly corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
6
18
1
Order By: Relevance
“…The high frequency of tetracycline resistance (61.6%) observed in this study differed significantly ( p < 0.001) from the resistance to tetracycline (19.6%, 10/51) observed in poultry by Stone et al (2013). Another study on sheep and goats in Grenada by Stone et al (2014) revealed resistance of Campylobacter isolates to tetracycline (30.8%, 4/13), which is also significantly lower ( p = 0.005) than the observation in this study.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…The high frequency of tetracycline resistance (61.6%) observed in this study differed significantly ( p < 0.001) from the resistance to tetracycline (19.6%, 10/51) observed in poultry by Stone et al (2013). Another study on sheep and goats in Grenada by Stone et al (2014) revealed resistance of Campylobacter isolates to tetracycline (30.8%, 4/13), which is also significantly lower ( p = 0.005) than the observation in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…most of the isolates belonged to ST-828 CC, which is mainly associated with previously reported isolates from agricultural and environmental sources and human clinical cases (Sheppard et al, 2010b). In Grenada, both Stone et al (2013) and Miller et al (2010) identified Campylobacter clones that belonged to the ST-828 CC in poultry; however, none of the STs in this present study was detected in their studies, nor in other animals, including goats and sheep . Furthermore, researchers in other geographic areas have reported the presence of STs in the ST-828 CC in human, poultry, swine, and cattle (Sanad et al, 2011;Kashoma et al, 2014).…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…The degree of association between specific genotypes and drug resistance in Campylobacter and Salmonella strains remains a topic of debate. Some researchers reported that drug resistance is associated with specific genotypes (25)(26)(27)(28)(29), whereas others reported no such associations (30,31). Because the number of isolates analyzed in this study was limited, further studies should be conducted to elucidate the association between genotypes and drug resistance in Campylobacter more precisely.…”
Section: Discussionmentioning
confidence: 82%